Green remediation of lead (pb) from Pb-toxic soil by combined use of silicon nanomaterials and leguminous Lens culinaris L. plants - Tayyaba Naz; Muhammad Mazhar Iqbal; Bilal Raza; Muhammad Asad Mubeen; Muhammad Ather Nadeem; Abdullah Ahmed Al-Ghamdi; Mohamed S Elshikh; Muhammad Rizwan; Rashid Iqbal (Scientific Reports)
Abstract Lead (Pb) toxicity is a major issue due to anthropogenic activities that is faced by farmers nowadays which inhibits plant growth and decreases crop yields. From contaminated soils, Pb absorbed by the plants and then ultimately enters into the food chain. Silicon (Si) can reduce Pb availability to plants and can be helpful in Pb immobilization in the soils. Moreover, Si in its nano-form, is expected to augment the beneficial attributes of applied Si. However, very little is known regarding the prospects of nano-Si application and leguminous lentil for alleviating the effects of Pb stress. To assess the effectiveness of bulk Si and nano-Si for reducing Pb toxicity and improving the yield of lentils, a pot study was conducted. Lentil variety Punjab Masoor 2020 was examined under normal and Pb toxic conditions as affected by applied Si and nano-Si. There were eight treatments comprised of different combinations of Si at 100 and 200 mg Si kg− 1 soil, and nano-Si at 125 mg kg− 1 soil, which were tested against Pb at 500 mg kg− 1 soil. A completely randomized design with factorial arrangements was applied along with three replications each. The result showed that Pb toxicity reduced the plant growth, yield, total chlorophyll contents, membrane stability index, relative water content, shoot fresh weight and dry weights of lentil. Whereas Si and nano-Si lessened the negative effect of Pb toxicity by significantly reducing its concentration in plant roots and shoot, and improved agro-physiological traits of lentil in normal and Pb-toxic soil conditions. In soil spiked with 500 mg kg− 1 Pb, the application of 100 and 200 mg bulk Si per kg of soil and 125 mg kg− 1 nano-Si reduced the Pb concentration in shoot by 31, 62 and 84% respectively over controls. In squat, the application of nano-Si most significantly (p ≤ 0.05) reduced the root and shoot Pb concentration in lentil.